2020
DOI: 10.1155/2020/1730492
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Potency, Antioxidant Effects, and Mode of Actions ofCitrus reticulataFruit Peel Hydroethanolic Extract, Hesperidin, and Quercetin in Nicotinamide/Streptozotocin-Induced Wistar Diabetic Rats

Abstract: This study is aimed at assessing the antihyperglycemic, antihyperlipidemic, and antioxidant effects of Citrus reticulata (C. reticulata) fruit peel hydroethanolic extract and two flavonoids, hesperidin and quercetin, in nicotinamide (NA)/streptozotocin- (STZ-) induced type 2 diabetic rats. In addition, GC-MS and HPLC-MS analyses of the extract were performed and the results indicated the presence of multiple flavonoids including hesperidin, quercetin, naringin, and polymethoxylated flavones (nobiletin and tang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 118 publications
9
52
0
2
Order By: Relevance
“…Thus, based on the results of the present study and of past publications, it can be suggested that the ameliorative effects of naringin and hesperidin, singly or in combination, on liver function and structural integrity may be attributed to their suppressive effects on the inflammation, oxidative stress, and apoptosis and to their stimulatory effects on antiinflammatory effects on antioxidant defense system (Figure 6). This suggestion was supported by previous publications which stated the antioxidant and anti-inflammatory effects of naringin and hesperidin in different diseased conditions and drug toxicities [65][66][67][68][69][70][71][72][73][74][75].…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 74%
“…Thus, based on the results of the present study and of past publications, it can be suggested that the ameliorative effects of naringin and hesperidin, singly or in combination, on liver function and structural integrity may be attributed to their suppressive effects on the inflammation, oxidative stress, and apoptosis and to their stimulatory effects on antiinflammatory effects on antioxidant defense system (Figure 6). This suggestion was supported by previous publications which stated the antioxidant and anti-inflammatory effects of naringin and hesperidin in different diseased conditions and drug toxicities [65][66][67][68][69][70][71][72][73][74][75].…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 74%
“…Similar results were found in ob/ob diabetic mice supplemented with the flavonoid nobiletin (200 mg/kg bw) [48]. Moreover, the oral administration of citrus fruit peel extracts and its constituting flavonoids naringin, naringenin, hesperidin and quercetin at a dose of 100 mg/kg bw for 4 weeks significantly recovered the suppressed mRNA expressions of GLUT-4 and IRβ-subunit in the adipose tissue of nicotinamide (NA)/streptozotocin-STZ/NA-induced type 2 diabetic rats [49,50]. Accordingly, the improved insulin sensitivity in the adipose tissue had potent anti-hyperglycemic and anti-hyperlipidemic effects in STZ/NA-induced diabetic rats.…”
Section: Effects Of Flavonoids On Insulin Signaling In T2dmentioning
confidence: 99%
“…Nicotinamide (NA)/streptozotocin (STZ)‐induced DM is most commonly used as animal model of T2DM in rats to validate the effect and to scrutinize the mechanisms of action of new therapeutic agents. In this model, there are both moderate impairment in insulin secretion and insulin resistance, which is a characteristic feature of T2DM (Ali et al., 2020; Gorinstein et al., 2007; Singh & Singh, 2010; Zhou et al., 2009).…”
Section: Introductionmentioning
confidence: 99%